Mg++ - and Ca++-Induced Platelet Aggregation and ADP - Cronberg, S; Caen, J. P (Thrombosis and Haemostasis, 1970)
Reports on platelet aggregation after addition of calcium or magnesium to EDTA- PRP or platelet suspensions were confirmed. An aggregating principle was found in the EDTA-plasma and the supernatant of the platelet suspensions. Aggregation by magnesium in a platelet suspension was inhibited by adenosine and phosphoenol- pyruvic acid and pyruvate kinase, which suggested that the active principle was identical with ADP. Degradation of ADP in EDTA plasma was blocked.It thus appears that aggregation induced by calcium or magnesium in EDTA-PRP and platelet suspension was due to accumulation of spontaneously liberated ADP, which was not degraded.